UJI LAPANGAN PENCACAH RIA BATAN UNTUK PENGUKURAN PROGESTERON SAPI DALAM PENENTUAN WAKTU PROSES INSEMINASI BUATAN - Wiranto Budi Santoso; Wahyuni Z. Imran; I Putu Susila; Leli Yuniarsari (Jurnal Perangkat Nuklir, 2010)
Field Test of BATAN's RIA Counter for Cow Progeteron Measurement in Determination of Artificial Insemination Time. The field test of RIA BA TAN counter for cow progesteron measurement in determination of artificial insemination time has been done. The test was conducted by comparing sampels meeasuring result between using BATAN's RIA counter and using imported RIA counter. Cow milk samples was taken from 40 cows which were owned by farmer under KUD Bayongbong, Garut, management. The samples were taken at 0-, 11-, and 21-days after artificial insemination process was conducted. In this study, the test was cemea out for two types of BATAN's IA counter (IP3 and IP8 types). Average deviation for BATAN's RIA counter type IP3 is 0.11. While average deviation for BATAN's RIA counter type IP3 is 0.15. From the above result could be concluded that counting results of BA TAN's RIA counters are equal to the imported one.   Field Test of BATAN's RIA Counter for Cow Progeteron Measurement in Determination of Artificial Insemination Time. The field test of RIA BA TAN counter for cow progesteron measurement in determination of artificial insemination time has been done. The test was conducted by comparing sampels meeasuring result between using BATAN's RIA counter and using imported RIA counter. Cow milk samples was taken from 40 cows which were owned by farmer under KUD Bayongbong, Garut, management. The samples were taken at 0-, 11-, and 21-days after artificial insemination process was conducted. In this study, the test was cemea out for two types of BATAN's RIA counter (IP3 and IP8 types). Average deviation for BATAN's RIA counter type IP3 is 0.11. While average deviation for BATAN's RIA counter type IP3 is 0.15. From the above result could be concluded that counting results of BA TAN's RIA counters are equal to the imported one.